2018
DOI: 10.1016/j.bbamem.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Modifying styrene-maleic acid co-polymer for studying lipid nanodiscs

Abstract: Recently, styrene-maleic acid copolymer lipid nanodiscs have become an increasingly popular tool for the study of membrane proteins. In the work we report here, we have developed a novel method for the efficient preparation of labeled nanodiscs, under chemically mild conditions, by modification of the hydrolyzed styrene-maleic acid copolymer. This protocol is designed to be easily accessible to biochemistry laboratories. We use this procedure to prepare various fluorescent nanodiscs labeled with different fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Following the initial incorporation of PagP and bacteriorhodopsin into SMA nanodiscs (11), a variety of membrane proteins have been studied using similar preparations (12,15,16). Further development has led to similar polymers with greater pH stability and decreased susceptibility to divalent metal cations, among other favorable properties (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Following the initial incorporation of PagP and bacteriorhodopsin into SMA nanodiscs (11), a variety of membrane proteins have been studied using similar preparations (12,15,16). Further development has led to similar polymers with greater pH stability and decreased susceptibility to divalent metal cations, among other favorable properties (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Exchange of polymers in addition to lipids is not unexpected. Recent studies have shown by fluorescently labelling SMA polymers, that in addition to the now-accepted lipid exchange between nanodiscs in solution [39] , [40] , there is also exchange of polymers between nanodiscs [51] . Furthermore, Langmuir balance and molecular dynamics studies of nanodisc self-assembly have demonstrated that nanodiscs form via an initial adsorption of polymers to the bilayer surface, prior to embedding into the hydrophobic core and subsequent solubilization [27] , [52] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, styrene-co-maleimide (SMI) is positively-charged and retains functionality at acidic pH, in contrast to the negative charge and alkaline working range of SMA; 28 styrene maleimide quarternary ammonium (SMA-QA) forms relatively large nanodiscs (∼30 nm diameter) that remain stable between pH 2.5-pH 10; 29 diisobutylene-co-maleic acid (DIBMA) in which the styrene aromatic ring of SMA is replaced by the aliphatic diisobutylene thereby changing how the polymer interacts with the lipid in the nanoparticles 30 and thiolated SMA (SMA-SH) which can be derivatised or immobilised via the introduced thiol. 43 All of these 'second generation' polymers generate lipid nanoparticles in the complete absence of detergent so preserve the native lipid in close association with the membrane protein. This is particularly important for GPCRs, as it has been shown that they can be regulated by the juxtaposition of specific membrane lipids.…”
Section: Characterization Of the Slower Diffusing Component (τ D2 )mentioning
confidence: 99%